Hubungan Indeks Massa Tubuh (IMT) terhadap Siklus Menstruasi pada Remaja di Stikara Sintang - Dian Ika Pratiwi; Atri Rudtitasari; Arum Seftiani Lestari; Yunida Haryanti; Rizki Amartani; Tri Endah Suryani (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2024)
The aim of this research was to determine the relationship between body mass index (BMI) and the menstrual cycle in adolescents at STIKARA SINTANG. The menstrual cycle is a clinical sign of female reproductive function. Menstruation is a complex process involving several hormones, sexual organs, and the nervous system. Body mass index is very influential on menstrual disorders because if a person experiences certain hormonal changes which are marked by a marked decrease in body weight (underweight, BMI < 18.5). The test used was the Chi-square test so the results were (p=0.05, pvalue =0.015), meaning there was a significant relationship between BMI and the menstrual cycle.